The Organelle Genome Database Project (GOBASE). - Korab-Laskowska, M (1998)
The taxonomically broad organelle genome database (GOBASE) organizes and integrates diverse data related to organelles (mitochondria and chloroplasts). The current version of GOBASE focuses on the mitochondrial subset of data and contains molecular sequences, RNA secondary structures and genetic maps, as well as taxonomic information for all eukaryotic species represented. The database has been designed so that complex biological queries, especially ones posed in a comparative genomics context, are supported. GOBASE has been implemented as a relational database with a web-based user interface (http://megasun.bch.umontreal.ca/gobase/gobas e.html ). Custom software tools have been written in house to assist in the population of the database, data validation, nomenclature standardization and front-end design. The database is fully operational and publicly accessible via the World Wide Web, allowing interactive browsing, sophisticated searching and easy downloading of data.